2013
DOI: 10.1177/1368430213507321
|View full text |Cite
|
Sign up to set email alerts
|

Competitive representative negotiations worsen intergroup relations

Abstract: Representative negotiation affords a unique opportunity to regulate intergroup competition and conflict. Although past research has identified factors that shape representative negotiations, little is known about how such interpersonal representative negotiations influence broader intergroup relations. Here we investigate how the representative negotiation process can affect intergroup relations, irrespective of negotiation outcomes. In Experiment 1, competitive (as opposed to cooperative or neutral) communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The contribution of this experiment is threefold. First, we expand the burgeoning literature on representative negotiations, specifically filling the gap where research has mostly investigated single issue and/or simulated negotiations (Aaldering, Greer, van Kleef, & De Dreu, 2013; Saygi et al, 2014; Steinel et al, 2009; Steinel et al, 2010; van Kleef et al, 2007). Our research shows how representatives interact to reach joint agreement depending on the preferences of their constituency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of this experiment is threefold. First, we expand the burgeoning literature on representative negotiations, specifically filling the gap where research has mostly investigated single issue and/or simulated negotiations (Aaldering, Greer, van Kleef, & De Dreu, 2013; Saygi et al, 2014; Steinel et al, 2009; Steinel et al, 2010; van Kleef et al, 2007). Our research shows how representatives interact to reach joint agreement depending on the preferences of their constituency.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported satisfaction (adapted from Saygı, Greer, van Kleef, & De Dreu, 2014) with the agreement was measured with six items (“I am satisfied with the agreement,” “I think I made a good deal,” “I think a better result would have been possible” [reverse coded], “I am annoyed that the agreement is not better” [reverse coded], “I am happy with the agreement,” and “I am disappointed about the agreement” [reverse coded]). Answering ranged from 1 ( not at all ) to 7 ( very much ), Cronbach’s α = .93.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that positive contact with an individual outgroup member can generalize to the entire outgroup (e.g., Johnston and Hewstone 1992;Saygi et al 2014;Weber and Crocker 1983), and this effect has been found even in the absence of direct contact (e.g., Turner et al 2007). However, this generalization process is most likely when group membership is made salient (Vivian et al 1997), such as by the prototypicality of the outgroup members (Oakes and Turner 1986;Oakes et al 1991).…”
Section: Representative Prototypicalitymentioning
confidence: 93%
“…Representative negotiation involves a two-level situation, in which the negotiation among individual representatives is embedded in a broader intergroup context, and the broader intergroup relations in turn depend on the way representatives negotiate (e.g., Knowles and Bassett 1976;Lickel et al 2000;Saygi et al 2014). Especially the second component, or the degree to which representatives' behaviors impact broader intergroup relations, is poorly understood .…”
Section: Bottom-up Effects Of Representative Cooperation On Intergroumentioning
confidence: 99%
See 1 more Smart Citation